Reduced graphene oxide/boron nitride composite film as a novel binder-free anode for lithium ion batteries with enhanced performances - Li, Hongling (2015)
Reduced graphene oxide (rGO)/boron nitride (BN) composite films were successfully fabricated by facile vacuum filtration and subsequent thermal treatment. Their morphology, structure and electrochemical performance were systematically characterized by field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, Raman spectroscopy, cyclic voltammetry, galvanostatic charge/discharge and electrochemical impedance spectroscopy. Importantly, the as-prepared rGO/BN composite film with a 2 wt.% BN content as binder-free anode material for lithium ion batteries (LIBs) exhibited a high reversible capacity of 278 mAh·g−1 at a high current density of 100 mA·g−1, high rate capability, and high capacity retention over the first 200 cycles. The enhanced electrochemical performances of rGO/BN composite film are attributed to the unique structure and the synergistic effects between layered BN and graphene, which favored electrolyte penetration and buffered the volume expansion during the lithiation and delithiation process. In addition, this work not only provides a versatile strategy for fabrication of other graphene-based films, but also shows the potential promise of rGO/BN composite film for other energy storage devices.